PENGARUH RETURN ON ASSET, SECURE DAN MATURITY TERHADAP RATING SUKUK - M. Siddiq Al Haraqi; Endang Surasetyo Ningsih (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This research was conducted at the companies that are listed on the Indonesia stock exchange publishes the sukuk as well as listed on the PT Pefindo, with the aim to test the influence of the financial aspects as measured by Return on Asset ratio (ROA) and aspect non-financial as measured by the secure and maturity againts rating sukuk. The number of samples used are as much as 9 companies that observed for 4 years, with the data analysis techniques used are ordinal logistic regressi on analysis. The results showed that simultaneously ROA, secure, and maturity rating to sukuk, with the magnitude of the influenceof 25,3%, whilw partially ROA and influential maturity positvely and significantly to rating sukuk, and secure influential not significant againts the ratings of sukuk